Estimating microplastic emissions from offshore wind turbine blades in the Dutch North Sea - M. Caboni; A. E. Schwarz; H. Slot; H. van der Mijle Meijer (Wind Energy Science)
The continued expansion of offshore wind energy raises concerns regarding the microplastics released from wind turbine blades due to leading edge erosion. Currently, the literature lacks reliable and transparent estimates of microplastic formation and emissions from wind turbines. To bridge this knowledge gap, we employed state-of-the-art models to analytically evaluate the release of microplastics resulting from wind turbine blades' leading edge erosion. This was achieved by integrating measured offshore weather data with a fatigue-based erosion model. We then applied and extrapolated this methodology to estimate microplastic emissions from all offshore wind turbines installed in the Dutch North Sea and compared these estimates to other sources of microplastics in the Netherlands. Our estimates indicate that microplastic emissions from a modern 15 MW offshore wind turbine equipped with a polyurethane-based leading edge protection system are approximately 240 g yr−1. Using this value, we estimated the current emissions from all wind turbines installed in the Dutch North Sea. Our projections suggest that the current emissions from Dutch offshore wind turbine blades, amounting to 100 kg yr−1, are approximately 1000 times lower than the total offshore microplastic emissions in the Netherlands when considering other sources, such as the paints and coatings of marine vessels.